Innate immunity in HIV‐1 infection: epithelial and non‐specific host factors of mucosal immunity‐ a workshop report. (April 2016) - Nittayananta, W; Weinberg, A; Malamud, D; Moyes, D; Webster‐Cyriaque, J; Ghosh, S
Abstract : The interplay between HIV‐1 and epithelial cells represents a critical aspect in mucosal HIV‐1 transmission. Epithelial cells lining the oral cavity cover subepithelial tissues, which contain virus‐susceptible host cells including CD4 + T lymphocytes, monocytes/macrophages, and dendritic cells. Oral epithelia are among the sites of first exposure to both cell‐free and cell‐associated virus HIV‐1 through breast‐feeding and oral–genital contact. However, oral mucosa is considered to be naturally resistant to HIV‐1 transmission. Oral epithelial cells have been shown to play a crucial role in innate host defense. Nevertheless, it is not clear to what degree these local innate immune factors contribute to HIV‐1 resistance of the oral mucosa. This review paper addressed the following issues that were discussed at the 7th World Workshop on Oral Health and Disease in AIDS held in Hyderabad, India, during November 6–9, 2014: (i) What is the fate of HIV‐1 after interactions with oral epithelial cells?; (ii) What are the keratinocyte and other anti‐HIV effector oral factors, and how do they contribute to mucosal protection?; (iii) How can HIV‐1 interactions with oral epithelium affect activation and populations of local immune cells?; (iv) How can HIV‐1 interactions alter functions of oral epithelial cells?